2000
DOI: 10.1111/j.1348-0421.2000.tb02522.x
|View full text |Cite
|
Sign up to set email alerts
|

Blockade ofSalmonella enteritidisPassage across the Basolateral Barriers of Human Intestinal Epithelial Cells by Specific Antibody

Abstract: Antibodies specific to Salmonella enteritidis (S.E.) were obtained from immunized egg yolk, and their protective effects against S.E. were studied by using monolayer-cultured human intestinal epithelial cells, Caco-2 and T84. The Salmonella adherence and entry to the cells were partially inhibited by the antibodies. The antibodies inhibited the decrease in transepithelial electrical resistance (TEER) of the intestinal epithelial monolayers and IL-8 secretion of the cells induced by S.E. invasion. Also, the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Such observations agree with the reported results (23) even if in the present assay's nonspecific IgY was used. In the cited in vitro study of adhesion (23), the anti-S. enteritidis antibodies were unable to completely block the adhesion of Salmonella, and the antibody binding did not suppress the multiplication of bacteria inside the cells.…”
Section: Resultssupporting
confidence: 94%
“…Such observations agree with the reported results (23) even if in the present assay's nonspecific IgY was used. In the cited in vitro study of adhesion (23), the anti-S. enteritidis antibodies were unable to completely block the adhesion of Salmonella, and the antibody binding did not suppress the multiplication of bacteria inside the cells.…”
Section: Resultssupporting
confidence: 94%
“…Four weeks after the bacterial challenge, hens were given daily a supplemented feed of 15% (w/w) of either non-immunized egg yolk powder or immunized egg yolk powder for 28 days. Oral administration of both powders resulted in a rapid decrease in the number of S. enteritidis in faeces and an elimination of the organism after 2 weeks of feeding (Brady et al, 2002;Sugita-Konishi et al, 2000).…”
Section: Igy Antibodies For Passive Immunization Against Enteric Infementioning
confidence: 99%
“…In one study, it was revealed that sera against Salmonella Enteritdis LPS, but not flagella, prevented entry of the bacterium in Hep-2 cells (Iankov et al 2002). The use of polarized Caco-2 and T84 cells demonstrated that invasion was inhibited by antisera to both Salmonella Enteritidis flagella and formalin-inactivated Salmonella Enteritidis (Sugita-Konishi et al 2000). Similarly, antibodies against Salmonella Typhimurium LPS have blocked S. Typhimurium invasion in MDCK cells (Michetti et al 1994;Forbes et al 2008).…”
mentioning
confidence: 93%